Cocoa flavanols and blood pressure reduction: Is there enough evidence to support a health claim in the United States?. (January 2019) - Wang, Yidi; Feltham, Bradley A.; Suh, Miyoung; Jones, Peter J.H.
Abstract: Background: Cocoa-containing food products are getting recognized as a blood pressure (BP) controlling food choice. The beneficial effect of cocoa on BP is attributable to its high content of flavanols, which are composed of epicatechin, catechin, and procyanidins. The main mechanism by which cocoa flavanols reduce BP is increasing nitric oxide. With a high prevalence of hypertension in the North America, a health claim petition on cocoa flavanols may be considered within the US framework, in order to allow people to make better food choices. Scope and approach: The objective of this review is to evaluate whether there is sufficient evidence to support a BP-lowering health claim for cocoa flavanols under the US Food and Drug Administration (FDA)'s jurisdiction. Seventeen human intervention studies examining the effect of cocoa flavanols on BP were identified, with nine studies in normotensive participants, and eight studies in hypertensive participants. All studies were assessed for methodological quality based on the outline provided by the FDA. Key findings and conclusions: Nine out of the 17 studies reported a BP-lowering effect of cocoa flavanols. This indicates the evidence of cocoa flavanols on BP reduction was conflicting. Only a few studies presented as high quality. The optimal dose of cocoa flavanols and long-term effect of cocoa flavanols on BP remain to be clarified. Therefore, within the US health claims system, an authorized health claim should not be passed, but a qualified health claim that is supported by low evidence may be attributed to cocoa flavanols and BP reduction. Highlights: Consumption of cocoa flavanols has been shown to reduce BP. The relationship between cocoa flavanols and BP is examined based on the US FDA health claims systems. Inconsistent evidence exists on the effect of cocoa flavanols on BP. Few studies are of high quality, and several uncertainties that must be addressed before passing the health claim. An authorized health claim should not be allowed, but a qualified health claim with a category "C" may be allowed.